1997
DOI: 10.1097/00000539-199701000-00028
|View full text |Cite
|
Sign up to set email alerts
|

The Duration of Impairment of Autonomic Control After Anticholinergic Drug Administration in Humans

Abstract: Impaired parasympathetic control of heart rate is associated with increased incidence of cardiac dysrhythmias and ischemia. Anticholinergic drugs, commonly administered during reversal of neuromuscular blockade, suppress parasympathetic control in the early postoperative period. This could potentially be detrimental in patients at risk of cardiovascular complications. The duration of parasympathetic impairment by two anticholinergic drugs were compared in this double-blind randomized cross-over study. Fourteen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 18 publications
1
18
0
1
Order By: Relevance
“…At the end of surgery, just prior to the occurrence of the cardiac arrest, the patient received glycopyrronium and neostigmine for reversal of the neuromuscular blockade. In two placebo-controlled studies (12,13), glycopyrronium was shown to markedly decrease the baroreceptor sensitivity and high-frequency heart rate variability. Such changes are indicative of an impaired parasympathetic control of heart rate, which is associated with an increased incidence of arrhythmias (12,13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of surgery, just prior to the occurrence of the cardiac arrest, the patient received glycopyrronium and neostigmine for reversal of the neuromuscular blockade. In two placebo-controlled studies (12,13), glycopyrronium was shown to markedly decrease the baroreceptor sensitivity and high-frequency heart rate variability. Such changes are indicative of an impaired parasympathetic control of heart rate, which is associated with an increased incidence of arrhythmias (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…In two placebo-controlled studies (12,13), glycopyrronium was shown to markedly decrease the baroreceptor sensitivity and high-frequency heart rate variability. Such changes are indicative of an impaired parasympathetic control of heart rate, which is associated with an increased incidence of arrhythmias (12,13). In another study, a marked prolongation of the QTc interval occurring during the first 2 min after the injection of various anticholinesterase-anticholinergic drug combinations was found (14).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the duration of parasympathetic impairment was compared after the use of two anticholinergic drugs, atropine and glycopyrronium. Both agents suppress parasympathetic control in the early postoperative period, and impaired parasympathetic control of heart rate is associated with increased incidence of cardiac arrhythmias and ischaemia . Parlow et al.…”
Section: Effect Of Anaesthesiamentioning
confidence: 99%
“…Administration of atropine is the common method to investigate tonic vagal activity. Spectral analysis of HRV has shown that anticholinergic drugs generally decrease the HF power of HR and blood pressure variability in humans (Pomeranz et al, 1985; Parlow et al, 1997). While low doses of atropine cause a decrease in HR and an increase in HRV, higher doses cause an increase in HR and a decrease in HRV (reviewed in Lewis et al, 2006).…”
Section: Discussionmentioning
confidence: 99%